Improving outcomes in acute and chronic periprosthetic hip and knee joint infection with a multidisciplinary approach. (2021) - Biddle, M.; Kennedy, J. W.; Wright, P. M.; Ritchie, N. D.; Meek, R. M. D.; Rooney, B. P.
No abstract available